Flann O’Brien Gallows humour - Borg, Ruben 1975-; Fagan, Paul (Cork University Press, 2020)
Intro -- Half Title -- Title -- Copyright -- Contents -- Acknowledgements -- List of abbreviations -- Notes on contributors -- Editors' introduction -- Part I. Body Politics -- 1. Everybody Here Is under Arrest: Translation and politics in Cruiskeen Lawn -- 2. 'nothing in the world would save me from the gallows': O'Nolan and the death penalty -- 3. Carnival and Class Consciousness: Bakhtin and the Free State in At Swim-Two-Birds -- 4. Spare-Time Physical Activities: Cruiskeen Lawn, the GAA and the Irish modernist body -- 5. The Soft Misogyny of Good Intentions: The Mother and Child Scheme, Cruiskeen Lawn and The Hard Life -- Part II: Failing Bodies -- 6. 'Where you bin, bud?' Myles na gCopaleen's disappearing act -- 7. 'the situation had become deplorably fluid': Alcohol, alchemy and Brian O'Nolan's metamorphoses -- 8. 'the tattered cloak of his perished skin': The body as costume in 'Two in One', At Swim-Two-Birds and The Third Policeman -- 9. 'Veni, V.D., Vici': Flann O'Brien, sexual health and the literature of exhaustion -- 10. Abject Bodies: Brian O'Nolan and immunology -- Part III: Bodies of Writing -- 11. Reading the Regional Body: Disability, prosthetics and Irish literary tradition in The Third Policeman and Molloy -- 12. Law and Violence in Ferguson's Congal, Yeats's The Herne's Egg and O'Brien's At Swim-Two-Birds -- 13. 'sprakin sea Djoytsch?' Brian Ó Nualláin's Bhark i bPrágrais -- 14. Flann O'Brien, the Absurd and the Authenticity of Death -- 15. 'the essential inherent interior essence': The Third Policeman and early modern ontologies -- 16. Origin, Iterability and Violence in The Third Policeman -- Notes -- Bibliography -- Index -- Backcover